A Finite Element Analysis of The Rectangle Spline Broach - Guangguo Zhang; Jing Sheng; Feng Wang (Institute of Advanced Engineering and Science, 2012)
In the traditional design,the impact tools of broach maybe unable to achieve the requirements for the processing precision,or even occur the situation of partial fracture due to a exaggerated partial deformation.In this article,by using Pro/E we complete the 3D solid modeling and the dimensional parameterization of the impact tools for rectangle spline broach,then import the 3D model into ANSYS,to analyze and solve the whole process of load and deformation at work.It can effectively improve the machining accuracy and the reliability of broach, shorten the design cycle and reduce cost. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1651